Energy conservation in query driven wireless sensor networks - Snigdh, Itu; Surani, Sagar S.; Sahu, Nilesh K. (Microsystem technologies : sensors, actuators, systems integration, 2021)
Network topology used to connect sensor nodes is important factor in wireless sensor networks (WSNs) that affect the energy usage of any network. Proper topology connection thereby reduces energy usage of network by reducing number of packet transmissions. Therefore node connection must be optimized in wireless sensor networks. Hence we introduce a new multiple tree based architecture of sensor network, comprising of heterogeneous nodes, to develop an energy efficient query processing WSN application. This article proposes Multi-tree and Multiple-tree algorithms for improving network parameters in the usual data collection WSN application scenarios. A multi-tree simply suggests a strategy where similar parameter type sensors are arranged in a tree based topology so as to reduce the energy consumption as well as the end to end delay in data communication. The Multiple-tree exemplifies a more effective way of query result propagation in data centric applications where delay requirements are not very stringent.